On the evolution of Cs droplets in SIMS craters. (27th October 2014) - Giordani, Andrew; Tuggle, Jay; Winkler, Christopher; Hunter, Jerry; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; Lee, Jae Cheol; Yi, Keewook; Hong, Tae Eun
<x xml:space="preserve">Abstract</x> The evolution of cesium droplets on silicon by Cs ion bombardment has been studied. For this work, a (100) Si substrate was sputtered with a 5 keV Cs+ primary ion beam at 45° until steady state was established. The evolution of Cs droplets was investigated under in situ O2 (oxygen jet) and ex situ atmospheric exposure conditions for controlled times. Additionally, the effect of sample heating on Cs droplets was also studied. The techniques used to characterize the Cs droplets were scanning electron microscopy with energy dispersive spectroscopy and X‐ray photoelectron spectroscopy. Our results indicate that Cs droplets evolve through a series of different morphologies before reaching their final form, and the rate of evolution depends strongly on environment (O2 or atmosphere) and the length of exposure. Copyright © 2014 John Wiley & Sons, Ltd.